UAV-enabled integrated sensing and communication:architecture, techniques, and future vision - Chenxi LIU; Rui MA; Mugen PENG (Dianxin kexue)
UAV emergency communication has been regarded as a typical application of the sixth generation mobile communication system (6G), and it can be flexible deployed and provide on-demand services.Meanwhile, integrated sensing and communication (ISAC) is a key feature and enabling technology for 6G.With the aid of the ISAC techniques, the spectral efficiency and the sensing accuracy of UAV emergency communication can be improved, while the system costs can be simultaneously reduced.However, how to efficiently integrate the ISAC techniques into the UAV emergency communication remains a hot and challenging research issue for both the academia and industry.Against these backdrops, a UAV-enabled ISAC architecture was proposed.Then, the fundamental principles that supported the proposed architecture were discussed.Finally, the future directions and challenges in UAV-enabled ISAC were provided.